ENVIROTMENT IMPACT IN THE MANAGEMENTOF SWALLOW’S NEST CULTIVATION IN TALANG RIMBA VILLAGE, CENGAL DISTRICT, OKI DISTRICT - Rosianty, Yuli; Syahroni, S.P, M.Si, Sasua Hustati; Muammar, Muammar (Universitas Muhammadiyah Palembang, 2024)
This research was carried out with the aim of analyzing the management of swallow's nest cultivation and analyzing the impact of management of swallow's nest cultivation on the environment in Talang Rimba Village, Cengal District, Ogan Komering Ilir Regency. The method used in this research was the Quantitative Descriptive method. Based on the conclusions, 50.63% of Talang Rimba Village respondents understand and know about the management of swallow's nest (Collocalia fuciphaga) cultivation (including: planning, implementation and supervision), regarding building ownership, location of swallow's nest (Collocalia fuciphaga) buildings, cultivating insects for food for swiftlets (Collocalia fuciphaga), processing swallow waste waste (Collocalia fuciphaga) and how to deal with pests that attack swiftlet nests (Collocalia fuciphaga). The management of swiftlet nest (Collocalia fuciphaga) cultivation has had a positive impact on the environment in Talang Rimba Village as much as 83.70%. The management of swiftlet nest (Collocalia fuciphaga) cultivation is: swiftlet nest (Collocalia fuciphaga) cultivation does not affect growth and plant development, timing of sound recordings can reduce the intensity of sound pollution and swallows (Collocalia fuciphaga) do not act as carriers of viruses or diseases from other birds.